Validation of picture story book “Tubuhku Berharga” as sexual education media for preschoolers - Pertiwi, Ratih Eka; Bhakti, Aditya Dwi Putra (Universitas Ahmad Dahlan, 2023)
Children and teenagers are at risk of being sexually abused targeted or performing risky sexual behavior. Appropriate sex education from their closest environment presented by parents or teachers is in demand. However, parents and teachers have limitations in giving sex education, especially in early childhood. Even though workshops or training for improving parents’ knowledge and skills are effective, specifically designed education tools are needed to support parents ad teachers in disseminating sexuality topics for kids. This research aimed to validate the picture storybook “Tubuhku Berharga” specially designed for preschoolers in two consecutive procedures. First, the content validation process to evaluate the design’s relevance and appropriateness. Next, a quasi-experiment protocol as an empirical validation process was conducted following the content validation. A one-group pretest-posttest design was used in a local kindergarten. The result demonstrated that the picture storybook “Tubuhku Berharga” is valid as a supporting tool in teaching sexuality matters to preschoolers. We suggested constructing other visual media with other topics in sexuality health, such as reproduction and body image that are age-suitable for preschoolers.